MAHABBAH DAN MA'RIFAH SERTA RELEVANSINYA BAGI KESALEHAN SOSIAL - Masturin Masturin (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2015)
Tasawuf Akhlaqi is a doctrine that explains the moral side from a person who performs taqorrub to her/his God by practicing Riyyadah self purification from bad morality. One discourse in tasawwuf akhlaqi which is most inspiring to the development to the better social life is mahabbah proposed by Rabi' ah al-' Adawiyyah and ma 'rifah proposed by Dzu al-Nun al Mishri and al-Ghazali. Both concepts appear having orientation to individual piety ofits actor. However, by the basic thought that culture and social dynamic are situated in dialectical process between its individual that able to give influence to their society, mahabbah and ma 'rifali that become a feature of individual piety are able to become the social or collective piety in the condition of the ability ofits actor to translate both concept that conformable with its nature and purpose.